Not‐So‐Innocent Anions Determine the Mechanism of Cationic Alkylators. Issue 10 (18th January 2021) - Taimoory, S. Maryamdokht; Cataldo, Vincenzo Alessandro; Schäfer, Andreas; Trant, John F.; Guterman, Ryan
Abstract: Alkylating reagents based on thioimidazolium ionic liquids were synthesized and the influence of the anion on the alkylation reaction mechanism explored in detail using both experimental and computational methods. Thioimidazolium cations transfer alkyl substituents to nucleophiles, however the reaction rate was highly dependent on anion identity, demonstrating that the anion is not innocent in the mechanism. Detailed analysis of the computationally‐derived potential energy surfaces associated with possible mechanisms indicated that this dependence arises from a combination of anion induced electronic, steric and coordinating effects, with highly nucleophilic anions catalyzing a 2‐step process while highly non‐nucleophilic, delocalized anions favor a 1‐step reaction. This work also confirms the presence of ion‐pairs and aggregates in solution thus supporting anion‐induced control over the reaction rate and mechanism. These findings provide new insight into an old reaction allowing for better design of cationic alkylators in synthesis, gene expression, polymer science, and protein chemistry applications. Abstract : Alkylating reagents based on thioimidazolium ionic liquids were synthesized and the influence of the anion on the alkylation reaction mechanism explored in detail using both experimental and computational methods.